Stentolith of common bile duct – a case report (Journal of Society of Surgeons of Nepal, 2016)
Foreign bodies acting as a nidus for stone formation are commonly reported but there are only few case reports on forgotten biliary stents. ERCP and stone removal with or without stenting for common bile duct stones are getting quite popular and there have been instances where the stent has been forgotten either by the patient or the physician.